Pengaruh Perbedaan Konsentrasi Maltodekstrin pada Starter Kering Susu Fermentasi Lactococcus Lactis D4 terhadap Kadar Air, Protein dan Rendemen dengan Metode Freeze Drying: Pengaruh Perbedaan Konsentrasi Maltodekstrin pada Starter Kering Susu Fermentasi Lactococcus Lactis D4 terhadap Kadar Air, Protein dan Rendemen dengan Metode Freeze Drying - Nurul Azizah; A. Hafiz Nasution; Indri Juliyarsi; Ade Sukma (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2026)
Dry starter has advantages due to its extended shelf life and efficient distribution process. The objective of this study was to evaluate the effect of different maltodextrin concentrations in the dry starter of fermented milk Lactococcus lactis D4 on moisture content, protein, and yield. Furthermore, the study aimed to determine the optimal concentration of maltodextrin. Skim milk and maltodextrin were utilized, and the drying process was carried out using the freeze-drying method. The method used in this study was an experimental design with a Completely Randomized Design (CRD), consisting of four treatments and five replications. The treatments applied were the addition of maltodextrin at concentrations of A (5%), B (10%), C (15%), and D (20%). The results showed that the addition of maltodextrin concentration had a significant effect (P<0.05) on moisture content, protein content, and yield. The maltodextrin concentration D (20%) exhibited the best results with a moisture content of 1.59%, protein content of 8.20%, and yield of 25.67%. The use of maltodextrin D (20%) is recommended in the production of dry starter of fermented milk Lactococcus lactis D4.